PERBEDAAN EFEKTIFITAS PEMBERIAN VITAMIN E 100 IU DENGAN ASPIRIN 81 MG UNTUK PENCEGAHAN PREEKLAMSIA PADA PRIMIGRAVIDA - Baktiyani, Siti Candra Windu; Wahjud, Imam (Fakultas Kedokteran Universitas Brawijaya, 2005)
Preeclampsia is a specific disturbance of human pregnancy, that diagnosed by the onset of hypertension and proteinuria in the third trimester. It occurs more in developing countries, due to the fact that developed countries have better prenatal care. The objective of this study was to assess the difference effectiveness of preventing preeclampsiaand giving vitamin E 100 iu and aspirin 81 mg. This study used prospective with single randomaised clinical trial. The place of this study is on Maternity care unit of RSUD Dr. Saiful Anwar Malang from October 2000 to October 2001. Fourty samples primigravidas between the age of 19-35 years were used in this study. Twenty four samples were treated with vitamin E and 24 samples were treated with aspirin started atthe eighteenth weeks of pregnancy until delivery. The changes, of blood presure, albuminuri and oedema were observed.The result showed that during the observation the incidence rate of mild preeclampsia of vitamin E was 4 samples or(16,7%), mild preeclampsia was 1 sample or (14,2%)by the time of the normal delivery. On the other hand, the mild preeclampsia of the control group of aspirin was 3 samples or (12,5%) and mild preeklampsia was 2 samples or (8,3%) at the normal delivery. There is no significant difference in preeclampsia occurance between vitamin E and aspirin group. Key words: Vitamin E, Aspirin, preeclampsia